'What's Going to Happen Now?' Changing Care Relations in a Psychosocial Context. (29th January 2019) - Cohen, Mark
Abstract : This paper advances a psychosocial hypothesis in understanding relations between recipients, and providers, of health and social care. In doing so, it draws on psychoanalytically informed work which considers the relation between the internal and external worlds and more generally the wider social context. The particular hypothesis in this paper relates to an understanding of an abusive form of relating underpinned by shame and envy. The paper suggests that exposure to these feeling states is more prevalent in a social world marked by increasing inequalities and environmental failures. This argument is underpinned with reference to qualitative and quantitative research, suggesting that antagonistic relationships are increasing and are part of a significant change in the culture. The argument is illustrated by a single detailed description of an initial consultation in an NHS psychotherapy service. An examination of the social context suggests how unhelpful or abusive relations may be manifest between health care providers and recipients, in care organizations and in the wider social world. This aspect of the argument is constructed with reference to relevant organizational and sociological literature. It is suggested that established relations of this type act to limit development, in this case a social development.